The true Argia difficilis Selys, 1865, with the description of Argia yungensis sp. nov. (Odonata: Coenagrionidae) - Garrison, Rosser W. (2007)
Argia yungensis sp. nov., a new species close to Argia difficilis, is described. Both species are illustrated and diagnosed and their distributions mapped. They can be distinguished by the morphology of male tori, cerci and paraproct, and female prothorax. Their distributions are allopatric, with Argia yungensis distributed along the foothill jungle of the Yungas rain forest from NW Argentina to Peru, and A. difficilis from Peru and Brazil to Venezuela across the lowland Amazon forest. Argia extranea forficula Fraser is synonymyzed with A. difficilis, and the latter is redescribed.